Evaluation of vascular density and structural changes in inflammatory bowel diseases - Sinan Bilgin; Ahmet Yekta Tüzün (European Journal of Inflammation, 2023)
Introduction The two most common types of inflammatory bowel disease (IBD) are ulcerative colitis (UC) and Crohn’s disease (CD). Although these diseases mainly affect the intestinal system, they can also affect other systems, especially the vascular system. The objective of this study is to evaluate ocular microvascular and structural changes in IBD. Methods A total of 42 patients with IBD (22 UC and 20 CD) followed in the gastroenterology clinic and 42 healthy controls matched for gender and age were enrolled in the study. All participants underwent optical coherence tomography angiography. Macular vessel density, central retinal, and choroidal thicknesses were measured. Results No significant differences were observed between IBD patients and control subjects as regards superficial vascular plexus density, deep vascular plexus density, and choriocapillaris vascular density, retinal and choroidal thickness in the macular area ( p > .05). Although not statistically significant, vascular density generally increased. On the other hand, retinal and choroidal thickness were decreased. Conclusion It could be said that there is a reactive increase in retinal vascular density and a decrease in retinal and choroidal thickness as a result of atherosclerotic changes in IBD.